Obsah psilocybinu a psilocinu v nĕkterých druzích hub - Stríbrný, J; Borovicka, J; Sokol, M (Soudni lekarstvi, 2003)
Psilocin and psilocybin are psychoactive components of mushrooms of the genus Psilocybe and many others (Panaeolus, Inocybe, Pluteus etc.). In our republic, several species of Psilocybe with a high content of these components can be found. In the present study, we give a semiquantitative content of psilocin and psilocybin in some of our mushrooms in dry substance (Psilocybe semilanceata, Psilocybe bohemica, Psilocybe arcana, Psilocybe cyanescens, Panaeolus acuminatus sensu Ricken, Inocybe haemacta and Pluteus salicinus). For quantification, the GC/MS instrumentation was applied. Psilocin and psilocybin were silylated by the derivatization agent N-methyl-N-trimet-hylsilyltrifluoroacetamide. As an internal standard, 5-methoxytryptamin was used. The results of this study prove the presence of at least three species of Psilocybe with a high content of psychoactive components growing in our republic: Psilocybe semilanceata, Psilocybe bohemica and Psilocybe arcana.
Keywords: Hallucinogens; Česká republika; psilocybin; Czech Republic; plynová chromatografie s hmotnostně spektrometrickou detekcí; Agaricales; Gas Chromatography-Mass Spectrometry; Psilocybin; halucinogeny